Interpretações de enfermeiros sobre o cuidado à demência no contexto hospitalar - Santos, Janici Therezinha (2007)
This research is aimed at investigating the interpretation of a nurse team in the context of the dementia care in hospitals. The world aging is a present phenomenon which is very debated by health professionals and researchers. The fast aging process observed in the developing countries as Brazil has not been supported by policies adequate to this population. It is known that chronic degenerative diseases along with aging cause staying for long days in a hospital. Families are broken-up when looking for a way out from the dependence that the elderly might present. It is necessary to choose family caregivers and others to give special attention to the elderly. Dementia is among the diseases which makes the patient very dependent as it develops. In the hospitals the elderly is admitted in medical-surgical clinic wards and stays among other patients who belong to different age groups and present several pathologies. It is up to the nurse, who is the nearest and most present professional for being longer with the patient and his family, to get institutional resources and adequate information so as to provide quality and decent assistance. Thinking just about the patient is not enough due to the fact that the family, as well as the family caregiver, also need support, mainly psychological, while they are escorting the elderly during the hospital admission. The nurse interpretations show what this work context is, which involves the elderly/family dependence disease problem. The professional nurse often works under overburden stress and in several occasions he/she needs institutional support and structure to give quality assistance. Also there are evidences concerning the conflict and afflicting situations which affect the families and family caregivers who reveal several aspects while dealing with so many difficulties related to the disease. Many of them do whatever is possible to stay with the patient, many are as old as the patient and need professional help. This research is aimed at showing the interpretations and, therefore, contributing to inform a certain reality, which may be one among many others, found in hospitals. Acknowledging the nurse value in searching information and decency in treating these elderly and families or family caregivers. Looking for ways and stimulating the team learning process so as to show that the care is in the Nurse s hand. This can not transferred to someone else!